A streetcar to be desired? The development of a new approach to measure perception of place quality in the context of tram network modernisation. (June 2021) - Diemer, Matthew J.; Currie, Graham; De Gruyter, Chris; Kamruzzaman, Md.; Hopkins, Ian
Abstract: Recent decades have seen a global resurgence in tram network development around the world. Despite a primary basis in transport, tram network development is increasingly framed as a spatial planning mechanism that is prioritised for its potential place-based outcomes. However, there has been limited academic research to investigate impacts of tram network development on community perception of place quality. This study contributes to the literature by presenting the results of 601 completed questionnaires investigating variation in perception of place quality between legacy and modernised tram streetscapes in Melbourne, Australia. Evidence demonstrates that modernised tram streetscapes were perceived to contain an enhanced physical design compared to their legacy counterparts. Additionally, modernised tram streetscapes were rated as higher quality locations overall that were more likely to facilitate a wide range of place-based activities and amenities. Overall findings provide evidence that tram modernisation can be framed as an opportunity for place quality enhancements, and appear to contradict some of the political complications that have played a role in stalling tram streetscape modernisation projects in Melbourne.